EVOLUTION OF ECONOMIC THOUGHT: A REVIEW OF THE LITERATURE AND ITS IMPLICATIONS FOR MODERN ECONOMIC POLICY - Reina A. Hadikusumo; Sabirin Sabirin; Solikah Nurwati (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The development of economic theories has evolved from the classical era to the modern era, and how these ideas influence economic policy formulation today. This research examines the major literature articulating the changes in economic paradigms, including classical, neoclassical, Keynesian, and modern economic theories such as Behavioural and Institutional Economics. The analysis shows that each approach has its own strengths and limitations as well as important contributions to our understanding of economic mechanisms. The implications of this evolution of thought for modern economic policy are significant, as policymakers must take into account various theoretical perspectives to design effective and adaptive policies. This multitheoretical approach allows for more comprehensive policies in addressing contemporary economic issues such as macroeconomic stability, inflation management, unemployment, resource distribution, and socio-institutional factors. Thus, this study emphasises the importance of flexibility and innovation in economic policy to achieve sustainable and inclusive economic development.